2021
DOI: 10.3390/recycling6030059
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Symbiosis through the Use of Biosolids as Fertilizer in Romanian Agriculture

Abstract: Biosolids’ use in agriculture is an example of industrial symbiosis. The application of biosolids (BS) in agriculture is considered one of the most sustainable sewage sludge (SS) management options, but the quality of biosolids has to meet certain requirements regarding the characteristics of the sludge, those of the land and of the type of crop. Web of Science database has been used to search for the relevant literature. The review of studies undertaken in order to determine the economic effects of the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Regarding sewage sludge biosolids, Ippolito et al 83 conducted a 22-year field study which found that biosolids improved soil chemical and biological health indices compared to inorganic fertilizers. Cioca et al 84 reviewed biosolids applications in Romania and found that they increased crop yields and reduced costs compared with SFs. A review by Lu et al 45 concurred that biosolids use in the USA produced "similar or higher yields than inorganic fertilizers, especially when applied for multiple years".…”
Section: ■ Discussionmentioning
confidence: 99%
“…Regarding sewage sludge biosolids, Ippolito et al 83 conducted a 22-year field study which found that biosolids improved soil chemical and biological health indices compared to inorganic fertilizers. Cioca et al 84 reviewed biosolids applications in Romania and found that they increased crop yields and reduced costs compared with SFs. A review by Lu et al 45 concurred that biosolids use in the USA produced "similar or higher yields than inorganic fertilizers, especially when applied for multiple years".…”
Section: ■ Discussionmentioning
confidence: 99%
“…Industrial ecology includes some specialized tools and techniques that can be used within industrial symbiosis. The network of physical processes and relationships between companies that transform raw materials and energy into finished products and waste is known as the "industrial metabolism" [28][29][30]. The industrial metabolism, in addition to biological systems, is based on the use of by-products to form closed cyclic systems that produce minimal waste and consume fewer natural resources and energy.…”
Section: Literature Reviewmentioning
confidence: 99%